Non-functioning pituitary adenoma: immunohistochemical analysis of 85 cases - Mahta, Ali; Haghpanah, Vahid; Lashkari, Anahita; Heshmat, Ramin; Larijani, Bagher; Tavangar, Seyed Mohammad (Folia Neuropathologica, 2007)
Pituitary adenomas without clinically active hypersecretion are summarized under the term non-functioning pituitary adenoma (NFPA). Since there are no specific serum markers, the differential diagnosis and treatment imply special difficulties. By using immunohistochemical methods we will have new insight into the nature and pathogenesis of these tumours. Ki-67 is a nuclear antigen detected by the monoclonal antibody MIB-1 and its labelling index (LI) is considered a marker of normal and abnormal cell proliferation. The aim of this study was to investigate the possible role of immunohistochemistry and MIB1-LI determination in NFPAs to predict tumoural behaviour and better management. In this clinicopathological study, 85 cases of NFPAs were analysed immunohistochemically. MIB1-LI was also determined in studied cases. Clinical presentation, treatment and follow-up data were also reviewed and the correlation between clinical and pathologic findings was established. Eighteen adenomas (21.2%) were immunoreactive to one or two adenohypophysial hormones of which 4 GH positive adenomas had aggressive behaviour (2 significant juxtasellar extensions and 2 recurrences). MIB-1 LI was more than 5% in only 5 cases including 2 invasive adenomas but with no evidence of recurrence. No significant statistical difference between clinical presentations in immunoreactive and non-immunoreactive NFPAs was observed except for unilateral temporal hemianopia which was more common in immunoreactive adenomas (P=0.022). NFPAs comprise several pathologically different types of tumours, some of which are potentially hormone producing, but some defects in hormone secretion or production of biologically inactive or insufficient amount of hormone may be the culprit in the lack of evidence of rising serum hormone levels. MIB-1 LI may be indicative of invasiveness but not a predictor of recurrence. Silent somatotropinomas may have more aggressive behaviour in comparison with other NFPAs.